HARMONISASI INTERAKSI ANTARA PEKERJA DAN PENGUSAHA SEBAGAI SEBUAH INVESTASI - Faida Normawati (Politeknik Kesejahteraan Sosial, 2005)
(Harmonization in Interaction Between The Labour and Owner, as The lnvestation) - Hasil Pembelajaran dari Sebuah Program Pengembangan. The transformation of industrial management paradigm from old corporate relation to be new corporate relation is the benefit condition, particularly for workers. Moreover, it is supported by environmental management and leadership system., in which the leader must has sustainable future vision, holistic and integrative thinking, good communicator, able to be mediator for all level and having learning orientation. The harmonic interaction will be raised if this condition able to be internalized in all elemant troughout industrial environtrnent. The workers become a partner and ddi not exploited again. Conflict between workers and management able to be minimalized.